Extracellular matrix of porcine pericardium: Biochemistry and collagen architecture - Sachsida Braga-Vilela, Antonella; Rosa Pimentel, Edson; Marangoni, Sergio; Hikari Toyama, Marcos [UNESP]; de Campos Vidal, Benedicto (Springer, 2008)
Pericardial tissue has been used to construct bioprostheses employed in the repair of different kinds of injuries, mostly cardiac. However, calcification and mechanical failure have been the main causes of the limited durability of cardiac bioprostheses constructed with bovine pericardium. In the course of this work, a study was conducted on porcine fibrous pericardium, its microscopic structure and biochemical nature. The general morphology and architecture of collagen were studied under conventional light and polarized light microscopy. The biochemical study of the pericardial matrix was conducted according to the following procedures: swelling test, hydroxyproline and collagen dosage, quantification of amino acids in soluble collagen, component extraction of the extracellular matrix of the right and left ventral regions of pericardium with different molarities of guanidine chloride, protein and glycosaminoglycan (GAG) dosage, sodium dodecyl sulfate-polyacrylamide gel electrophoresis and total GAG analysis. Microscopic analysis showed collagen fibers arranged in multidirectionally oriented layers forming a closely knit web, with a larger number of fibers obliquely oriented, initiating at the lower central region toward the upper left lateral relative to the heart. No qualitative differences were found between proteins extracted from the right and left regions. Likewise, no differences were found between fresh and frozen material. Protein dosages from left frontal and right frontal pericardium regions showed no significant differences. The quantities of extracted GAGs were too small for detection by the method used. Enzymatic digestion and electrophoretic analysis showed that the GAG found is possibly dermatan sulfate. The proteoglycan showed a running standard very similar to the small proteoglycan decorin.
Keywords: extracellular matrix; porcine pericardium; collagen; proteoglycan glycosaminoglycan; bioprosthesis